Colorimetric Assay to Quantify Macromolecule Diffusion across Endothelial Monolayers - Steve L. Duffy; Joseph T. Murphy (BioTechniques)
Endothelial “capillary leak”, the loss of vascular integrity in response to noxious stimuli, is characterized by extravasation of protein-rich fluid from capillary lumen into surrounding tissue interstitium. This increase in vascular permeability, in response to inflammatory mediators, correlates with endothelial cell contraction and the formation of intercellular gaps within the monolayer. However, in vivo assessment of paracellular solute flow between endothelial cells may be complicated by multiple uncontrolled parameters. In vitro examinations of endothelial barrier leak have relied on electrical impedence or macromolecule diffusion techniques to determine the details pertinent to capillary barrier function. In this report, a simple, sensitive, nonradioactive, colorimetric assay to quantify the leak of a labeled protein marker across endothelial monolayers is described. This procedure avoids the hazards of radioisotope labels and the technical limitations of electrical resistance technology.